Analysis and Application of Big Data in Social Media Marketing - Qin, Yumeng (International Journal of Global Economics and Management, 2024)
This paper discusses the importance and advantages of big data analysis and application in social media marketing. With the popularity of social media platforms, big data analysis provides enterprises with opportunities to deeply understand user needs, optimize marketing strategies and improve marketing effects. This paper introduces the current situation of social media marketing, and expounds in detail the application of big data analysis in user portrait analysis, user behavior analysis and marketing effect evaluation. Through big data analysis, enterprises can formulate more accurate marketing strategies, improve marketing accuracy, optimize user experience and improve marketing efficiency. However, big data analysis also faces challenges such as data quality and privacy protection, which requires enterprises to pay attention to data security and compliance in the process of application.